Immune reconstitution post allogeneic transplant and the impact of immune recovery on the risk of infection. Issue 8 (16th November 2016) - Mehta, Rohtesh S.; Rezvani, Katayoun
ABSTRACT: Infection is the leading cause of non-relapse mortality after allogeneic haematopoietic cell transplantation (HCT). This occurs as a result of dysfunction to the host immune system from the preparative regimen used prior to HCT, combined with a delay in reconstitution of the donor-derived immune system after HCT. In this article, we elaborate on the process of immune reconstitution post-HCT that begins with the innate system and is followed by recovery of adaptive immunity. Simultaneously, we describe how the tempo of immune reconstitution influences the risk of various infections. We explain some of the key differences in immune reconstitution and the consequent risk of infections in recipients of peripheral blood stem cell, bone marrow or umbilical cord blood grafts. Other factors that impact on immune recovery are also highlighted. Finally, we allude to various strategies that are being tested to enhance immune reconstitution post-HCT.